The Dominance of Borrowers and Savers Credit Unions - Westrup, Mário Nazzari; Camilo, Silvio Parodi Oliveira (Advances in Social Sciences Research Journal, 2022)
This paper addresses the determinants of dominance by resource borrowers or savers in credit unions in the southern region of Brazil. The study is a prevalence of previous and convergent work that discuss the dominance and its effects. In order to evaluate the influence of the determining factors on credit unions about the type of domination, we adopted panel date the multivariate analysis technique. The results of the study pointed out that the objects investigated present dominance of members who are credit borrowers, and present determinant factors that are significant and that influence the rate of domination of the borrower. The proposition becomes relevant by contributing with empirical evidence already existing in other contexts. Given the growing participation of credit unions in the economy, and their impact on local development. Conflict of interests of the participants allied to the analysis of an environmental, balanced or turbulent context, can influence the movements, policies or group arrangements. Investigations that deal with decisions and power relations between quota holders, whether as board members or even managers, in a dual or trial function appearing to be important in future studies.